2018
DOI: 10.1155/2018/3407821
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Bmal1 and Per2 in Mouse BMSC Osteogenic Differentiation

Abstract: The circadian clock is a system that controls endogenous time of organisms, and it regulates the physiology and behavior of bodies. The transcription factors Brain and Muscle ARNT-like Protein 1 (BMAL1) and Period2 (Per2) are components of the circadian clock, and they play vital roles in circadian clock function. Both Bmal1−/− mice and Per2−/− mice display obvious bone volume changes. In this study, we inhibited the expression of Bmal1 in bone marrow-derived mesenchymal stem cells (BMSCs) using a lentiviral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Recently, various studies have indicated that these circadian clock genes serve a crucial role in modulating the behavior of mesenchymal stem cells involved in bone homeostasis and rehabilitation. [34][35][36]38,[47][48][49] However, the conclusions of these findings are not always consistent. 36,50 One study reported that Bmal1 knockout mice have impaired BMSCs differentiation under osteogenic conditions, and a reduced number of both active osteoblasts and osteocytes 36 ; while another study observed an increase in osteoblast activity in Bmal1 knockout mice.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Recently, various studies have indicated that these circadian clock genes serve a crucial role in modulating the behavior of mesenchymal stem cells involved in bone homeostasis and rehabilitation. [34][35][36]38,[47][48][49] However, the conclusions of these findings are not always consistent. 36,50 One study reported that Bmal1 knockout mice have impaired BMSCs differentiation under osteogenic conditions, and a reduced number of both active osteoblasts and osteocytes 36 ; while another study observed an increase in osteoblast activity in Bmal1 knockout mice.…”
Section: Discussionmentioning
confidence: 91%
“…While previous studies have identified a correlation between the circadian clock and bone homeostasis, [34][35][36][37][38] an understanding of the underlying mechanism whereby the circadian clock to modulate bone and cartilage homeostasis and metabolism is pivotal to ensure a more accurate treatment time for chronic diseases, such as osteoporosis, osteoarthritis, or other age-related bone degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhou et al. (2018) reported that osteogenic differentiation of bone marrow stem cells (BMSCs) in vitro is enhanced when RNA interference techniques are used to inhibit the expression of Arntl/Bmal1 or Per2 , indicating that ARNTL/BMAL1 and PER2 negatively regulate the osteogenic potential of BMSCs and may have a synergistic effect on the osteogenic differentiation of BMSCs [33]. We show here that the proliferation of osteoblast derived from mPer2 m/m mice was enhanced compared with those of WT mice, suggesting that an absence of PER2 shortens the cell cycle and the biological clock.…”
Section: Discussionmentioning
confidence: 99%